KELAYAKAN FINANSIAL DAN STRATEGI PENGEMBANGAN AGROINDUSTRI SABUT KELAPA CV SUMBER SARI DI DESA LEMBENGAN KECAMATAN LEDOKOMBO KABUPATEN JEMBER - Fandy Adry Willy Putranto; Ebban Bagus Kuntadi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2019)
Coconut coir is the outermost part of the coconut which wraps the coconut shell. Agro-industry in Jember Regency which processes coconut fiber is located in Lembengan Village, Ledokombo District, Jember Regency. Production activities require the use of planned costs in order to get optimal profits with the investments that have been made, so that the flow of money or cash that is in the CV Sumber Sari agro-industry goes well and can avoid risks that result in income for the development of agro-industry.This study aims to determine: (1) the feasibility analysis of CV Sumber Sari coconut coir agroindustry in Lembengan Village, Ledokombo District, Jember Regency (2) sensitivity analysis of parameter changes that occur. Determination of the study area using purposive method, at the CV Sumber Sari agroindustry in Lembengan Village, Ledokombo District. The method of sampling is done intentionally or purposive sampling using certain criteria. The data used are primary and secondary data by using data collection methods in the form of observation, interviews (interviews), and documentation. The data was then analyzed using feasibility criteria analysis and sensitivity analysis. The results showed that 1) Coconut fiber Agroindustry CV Sumber Sari, Jember Regency is worth the effort. NPV value of Rp. 6.794.149.777. PI value or Net B / C of 6,7041. IRR value of 66,32%. PP value of 1 year 11 months 25 days (Bank Indonesia interest rate 6.50%). 2) Coconut coir agroindustry CV Sumber Sari, Jember Regency is not sensitive to changes in the variable cost of coconut fiber raw material increases by 100% and decreases in selling prices of products by 15% so that it is still viable for business.